Fa’liyah Istighdami al-Munaqasah al-Fiqhiyyah bil-‘Arabiyah fi Tanmiyati Maharatil Kalam bi Ma’had Darul Lughah Wadda’wah Bangil Jawa Syarqiyah (Bahsu Tajri’bi fi Fashal At Tsalist Assanawi fi Ma’had Darul Lughah Wa Da’wah) - Baharun, Segaf; Muhamad Solehudin; Munapi; Yusuf Arisandi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2021)
Observations and interviews that have been carried out by researchers at some Mustawa tsanawi that some students are not sufficient with the existing methods that students learn and some students want new methods, because some students want to allow them to express what they want and expand their thinking, and therefore the researcher put a new way besides the method used by the pesantren, and because the researcher saw that some students wanted to expand their thinking, and improve the way they expressed themselves on speaking skills, and by looking at the conditions that occurred, the researcher wanted to test the effectiveness of using munaqosah fiqih with Arabic to improve speaking skills in the third grade Tsanawi at the Darullughah Wadda'wah Bangil Pasuruan Islamic boarding school, and the researcher wrote two problem formulations: how to use munaqosah fiqih in Arabic to improve skills speaking in the third grade Tsanawi at the Darullughah Wadda'wah Bangil Pasuruan Islamic boarding school? And what is the effectiveness of munaqosah fiqih with Arabic to improve speaking skills in the third grade Tsanawi at the Darullughah Wadda'wah Bangil Pasuruan Islamic boarding school ?. And the approach used by the researcher is a quantitative approach, and in terms of its implementation, it uses an experimental method, because the researcher tests the hypothesis and the existing variables, and the researcher collects data by observation, interview, and test. The researcher draws the conclusion of this study that the degree T Count in this study is 4.63 greater than the degree T Table at the standard 5% (2.0), and from the degree T Table on the standard 1% (2.66), it is known that the hypothesis in this study is accepted, and this suggests that the use of Munaqosah Fiqih with Arabic in Arabic learning to develop EFFECTIVE speaking skills. Keyword: Musaqosah Fiqih in Arabic; Speaking Skills.